Dynamic multimedia content delivery based on real-time user emotions: multichannel online biosignals towards adaptative gui and content delivery - Vasco Vinhas (2009)
Recently topics such as affective computing and multichannel multimedia distribution have gained the attention and investment of both industry and academics. The proposed system joins these domains so that ubiquitous system can be potentiated by means of online user emotion assessment based on real-time user's biosignals. It was used IAPS as a emotional library for controlled visual stimuli and biosignals were collected in real-time - heartbeat rate and skin conductance - in order to online assess the user's emotional state through Russell's Circumplex Model of Affect. To improve usability and session setup, a distributed architecture was used so that software models might be physically detached. The conducted experimental sessions and the validation interviews supported the system's efficiency not only in real-time discrete emotional state assessment but also considering the emotion inducing process. The future work consists in replicating the success in multi-format multimedia contents without pre-defined emotional metadata.